2022
DOI: 10.3389/fpsyg.2022.885515
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Ethical Leadership and Employee Job Satisfaction: The Mediating Role of Media Richness and Perceived Organizational Transparency

Abstract: Ethical leadership (EL) is a vital component driving firms’ practice, significantly affecting employee satisfaction (ES). The objective of this study was to investigate the relationship between EL and employee job satisfaction. Moreover, the study investigates the mediating effect of media richness (MR), perceived organizational transparency (OT) on EL, and ES. In addition, the study used a convenient sampling technique for collecting the data from 276 employees working in the service sector of Macau. Essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 71 publications
0
15
0
1
Order By: Relevance
“…In previous studies, EL was usually associated with significant job results (Ruiz-Palomino et al, 2013). As per Guo (2022), the result shows that there is a significant and positive relationship between ethical leadership and employee satisfaction. However, the study found that ethical leadership improves employee job satisfaction, hence influencing personal behavior (Guo, 2022;Işik, 2020).…”
Section: Ethical Leadership and Job Satisfaction Relationshipmentioning
confidence: 63%
See 1 more Smart Citation
“…In previous studies, EL was usually associated with significant job results (Ruiz-Palomino et al, 2013). As per Guo (2022), the result shows that there is a significant and positive relationship between ethical leadership and employee satisfaction. However, the study found that ethical leadership improves employee job satisfaction, hence influencing personal behavior (Guo, 2022;Işik, 2020).…”
Section: Ethical Leadership and Job Satisfaction Relationshipmentioning
confidence: 63%
“…As per Guo (2022), the result shows that there is a significant and positive relationship between ethical leadership and employee satisfaction. However, the study found that ethical leadership improves employee job satisfaction, hence influencing personal behavior (Guo, 2022;Işik, 2020). Mustafa & Lines (2014) argued that the leader's characteristics and behaviors play an important role in improving employee JS and helping them develop a positive attitude about their work.…”
Section: Ethical Leadership and Job Satisfaction Relationshipmentioning
confidence: 88%
“…Ethics plays a vital role in improving individuals" work behaviour, action and conduct through enhancing their right thoughts and principals (Rabie & AbdulMalek, 2020). A good leader should be a moral character rather than managers" knowledge, expertise and strategic power (Guo K, 2022).The moral characteristics of an ethical leader are morally responsible, honest and visionary (Sharma et al, 2019). Therefore, moral leadership is a unique concept, which supports employee satisfaction.…”
Section: Ethical Leadership and Employee Engagementmentioning
confidence: 99%
“…Both public and private businesses should adopt the concept of ethical leadership to achieve global socioeconomic expansion in order to fulfill the expanding demand for workplace and organizations ethics. Furthermore, today's business leaders need to rethink and reevaluate what they areoffering, how they operate a business, who might be new participants to achieve better performance, new services, products, and so on (Guo, 2022).…”
Section: Introductionmentioning
confidence: 99%